Perspective—On the Need for Reliability and Safety Studies of Grid-Scale Aqueous Batteries. Issue 9 (28th May 2020) - Wittman, Reed M.; Perry, Mike L.; Lambert, Timothy N.; Chalamala, Babu R.; Preger, Yuliya
Abstract : Li-ion batteries currently dominate electrochemical energy storage for grid-scale applications, but there are promising aqueous battery technologies on the path to commercial adoption. Though aqueous batteries are considered lower risk, they can still undergo problematic degradation processes. This perspective details the degradation that aqueous batteries can experience during normal and abusive operation, and how these processes can even lead to cascading failure. We outline methods for studying these phenomena at the material and single-cell level. Considering reliability and safety studies early in technology development will facilitate translation of emerging aqueous batteries from the lab to the field.